Hole‐extraction layer dependence of defect formation and operation of planar CH3NH3PbI3 perovskite solar cells. Issue 2 (23rd December 2016) - Nguyen, Duc Cuong; Joe, Sung‐yoon; Ha, Na Young; Park, Hui Joon; Park, Ji‐Yong; Ahn, Y. H.; Lee, Soonil
Abstract : Three planar CH3 NH3 PbI3 (MAPbI3 ) solar cells having the same structure except a hole‐extraction layer (HEL) showed distinctive difference in operation characteristics. Analysis of frequency‐dependent capacitance and dielectric‐loss spectra of the three MAPbI3 devices showed two types of recombination‐loss channels with different time constants that we attributed respectively to interface and bulk defects. Discrepancy in defect formation among the three devices with a HEL of PEDOT:PSS, NiO x, or Cu‐doped NiO x was not surprising because grain‐size distribution and crystalline quality of MAPbI3 can be affected by surface energy and morphology of underlying HELs. We were able to quantify interface and bulk defects in these MAPbI3 solar cells based on systematic and simultaneous simulations of capacitance and dielectric‐loss spectra, and current–voltage characteristics by using the device simulator SCAPS. Defect density reduction is essential for efficient planar solar cells. Defect density in MAPbI3 layers, with respect to which an open‐cell voltage and a fill factor vary, can be investigated by using capacitance–frequency spectra. Abstract : The change of hole‐extraction layers in planar perovskite solar cells produced distinctive variations in the operation characteristics. Analysis of frequency‐dependent capacitance and dielectric‐loss spectra and device simulations showed that two types of recombination‐loss channels due to interface and bulk defects were responsible for degradation of solar cell performance. Quality of the perovskite layers, which is closely connected with defect distribution, was found to be affected by surface energy and morphology of the underlying hole‐extraction layers.